Investigating the function of coding polymorphisms within the TBX15-WARS2 locus associated with waist-hip ratio as a risk factor for metabolic syndrome - Zolkiewski, L (2023)
As prevalence of obesity and metabolic disorders increase, it is necessary to elucidate mechanisms driving body mass, body composition and energy homeostasis. Elevated waist-hip ratio (WHR) increases type 2 diabetes and cardiovascular disease risk. The TBX15-WARS2 locus contains several independent association signals for WHR adjusted for BMI (WHRadjBMI). However, whether these risk variants are functional remains to be determined. The aim of my DPhil was to characterise two potentially functional TBX15-coding polymorphisms, rs10494217 (p.H156N) and rs61730011 (p.M566R), at a cellular and organismal level to investigate their impact on TBX15 function in adipose tissue biology.